Job-scheduling via resource availability prediction for volunteer computational grids. (10th May 2011) - Zhang, Jun; Phillips, Chris
In a volunteer-based computational grid computing, one big challenge for effective job allocation is resource availability. As resources in this environment are volatile, matching guest jobs to suitable resources is very important. To improve scheduling, especially in terms of avoiding job failures due to resource unavailability, we propose a new job-scheduling algorithm called first-come-first-served plus predictor (FCFSPP). This scheduling algorithm is based on an existing resource availability prediction method that anticipates the future availability of resources to help make reliable job allocation decisions. According to the simulation results, FCFSPP does not only reduce the number of job failures but also maintain acceptable job throughput in volatile volunteer environments by providing reliable job allocation decisions.